Resilience of Grain Yield in China Under Climate Change Scenarios - Chou, Jieming; Sun, Mingyang; Xu, Yuan; Yang, Fan; Li, Jiangnan; Zhao, Weixing (Frontiers in Environmental Science, 2021)
As global warming issues become increasingly serious, grain yield and socioeconomic development have been seriously threatened. The key to ensuring grain yield is to recognize the risks caused by climate change. In this paper, the trends of temperature and precipitation over the next 30 years in China are analysed using CMIP6 under the SSP1-2.6, SSP2-4.5 and SSP 5-8.5 climate scenarios. The resilience indicators of grain yield are proposed for the first time. We find that the higher the emission concentration is, the greater the temperature increase will be and further northward the precipitation belt will move. Meanwhile, the resilience varies across different climate zones. The temperate monsoon climate zone has a stronger resilience to adapt to climate change compared to that of other areas. The resilience of the temperate continental and plateau alpine climate zones are moderate. However, the resilience of the subtropical and tropical monsoon climates zones are poor.